Teachers’ Challenges in Employing the Assessment Strategies Within Differentiated Learning - Dewi, Kadek Cahya (Universitas Pendidikan Ganesha, 2025)
In practical application, teachers often encounter obstacles in implementing assessment strategies with differentiated learning. This study aims to identify the challenges teachers face in applying assessment strategies in differentiated learning at SMP Negeri 1 Singaraja in the context of the Merdeka Curriculum. The approach is descriptive qualitative, with data collection techniques using unstructured interviews. The research subjects were English teachers with the criteria of having experience in assessing students, being willing to provide data, and facing challenges in implementing assessment strategies. Data analysis was conducted through the stages of data collection, data reduction by filtering and grouping main themes, descriptive and visual data presentation, and drawing conclusions by matching interview results. The study results indicate that teachers face three main challenges: large class sizes, time constraints, and a lack of resources and technological support. Large class sizes make it difficult for teachers to design assessments tailored to individual needs. Time constraints are an obstacle to planning and providing assessment feedback. Additionally, limited access to technology and differentiated instructional materials also hinder the implementation of practical assessments. This study is expected to serve as a reference for formulating more adaptive assessment strategies tailored to the diverse needs of students in the era of the Merdeka Curriculum.